2023
DOI: 10.1007/s40726-023-00284-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Green Areas on the Urban Sound Environment

Guillermo Rey-Gozalo,
Juan Miguel Barrigón Morillas,
David Montes González
et al.

Abstract: Purpose of Review Urban green spaces provide benefits for human health and well-being, among other properties, thanks to their ability to attenuate environmental pollutants. The sound environment is not healthy in most cities, and this situation has not changed in recent decades. These green spaces are potential quiet areas with good acoustic quality if they are designed and planned properly from a multidisciplinary perspective. Although the mitigating effects of green infrastructure have been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 124 publications
0
1
0
Order By: Relevance
“…For instance, Wang et al (2022), showed that plant community species, leaf area index, plant height, and biomass index are important factors contributing to high NAIC within forests [35]. This is also an important factor in regulating the comfort of the acoustic environment in the forest [36]. As for PM2.5 and PM10, research in Florence, Italy found that plant diversity in forests has a direct inhibitory effect on PM2.5 and PM10 [37].…”
Section: Differences In the Health Effects Of A Single Recuperative F...mentioning
confidence: 99%
“…For instance, Wang et al (2022), showed that plant community species, leaf area index, plant height, and biomass index are important factors contributing to high NAIC within forests [35]. This is also an important factor in regulating the comfort of the acoustic environment in the forest [36]. As for PM2.5 and PM10, research in Florence, Italy found that plant diversity in forests has a direct inhibitory effect on PM2.5 and PM10 [37].…”
Section: Differences In the Health Effects Of A Single Recuperative F...mentioning
confidence: 99%